Determining RE-AIM indicators for evaluating the Estratégia Amamenta e Alimenta Brasil (EAAB - Brazilian Breastfeeding and Complementary Feeding Strategy) - Daiane Sousa Melo; Sonia Isoyama Venancio; Gabriela Buccini (Universidade de São Paulo, 2024)
ABSTRACT OBJECTIVE To confirm the diagram of the program's impact pathways and Estratégia Amamenta e Alimenta Brasil (EAAB - Brazilian Breastfeeding and Complementary Feeding Strategy) core functions, and to determine indicators for evaluating EAAB. METHODS This is a qualitative study within the field of implementation research. Data collection included two focus groups with EAAB implementers, document analysis, and literature review. The analysis included a review of the participants' suggestions and two stages of reviewing the diagram and the names of the impact pathways and core functions. Questions for evaluating the EAAB were then constructed based on the confirmed diagram. The indicators of the RE-AIM framework (reach, effectiveness, adoption, implementation, maintenance) were adapted to the EAAB context. The evaluation questions were revised according to the RE-AIM domains and, finally, indicators were determined for each evaluation question. RESULTS This study advanced the analysis of EAAB implementation, defining 22 indicators for its monitoring and evaluation. Most of the indicators are already used in implementation, however, the analysis with the RE-AIM framework allowed the indicators to be updated to be more specific, measurable, and relevant to the desired objectives. CONCLUSION The results of the study support the pragmatic application of RE-AIM evaluation in health programs and encourage the planning of evaluation indicators for other child health and development programs in primary care.